The relation between mandibular symphysis and the Angle class in orthodontic treatment - Nobre, Ricardina; de Castro, Saúl Matos; Ponces, Maria João; Lopes, Jorge Dias; Ferreira, Afonso Pinhão (Medicine and Pharmacy Reports, 2022)
Objectives. Facial perception depends on the different components of the face. The chin is a striking anatomical structure in the individual’s identity and mandibular symphysis (MS) shape influences the adjacent soft tissue, determining facial harmony. In lateral cephalometry, the MS corresponds to the image of the mandibular body in its anterior curvature. It shape, inclination and thickness provide valuable information for orthodontic diagnosis and prognosis. Since facial features are associated with malocclusions, the present investigation aims to relate the height, thickness and inclination of the MS using Angle’s Class. Methods. 495 lateral incidence cephalograms of an orthodontic population were analyzed using a previously developed and tested software. The sample was randomly selected and the height, thickness and inclination of the MS were measured. The values were statistically analyzed (p ≤ 0.05). Results. The distribution according to Angle’s Class was 48.9% for Class I, 34.7% for Class II Division 1, 7.4% for Class II Division 2 and 8.9% for Class III. The MS height did not´t show significant differences between the three dental classes. The MS thickness was significantly increased in Class II Division 2 and Class I subjects (p = 0,037). The MS inclination was significantly less in Class III subjects when compared to Class I and Class II Division 1 (p ≤ 0.001). Conclusions. The MS presented variations, which may be associated with a natural compensation against malocclusion, influencing the position of the teeth and their relationship with the other dento-craniofacial structures and with consequences on the facial harmony.